The effect of classroom acoustic conditions on literacy outcomes for children in primary school: A review. Issue 1 (March 2022) - Mealings, Kiri
Literacy skills are essential for success in today's society. However, classrooms often have suboptimal acoustic conditions for learning. The goal of this review was to synthesize research assessing the effect of different classroom acoustic conditions on children's literacy. A comprehensive search of four online databases was conducted in August 2021. The search term was classroom AND (noise OR reverberation OR acoustics) AND (reading OR spelling OR writing OR literacy). Eighteen papers were deemed relevant for the review plus an additional seven from their references. The types of acoustic conditions that have been assessed, the types of measures used to assess literacy, and the effect of the acoustic conditions on children's reading, writing, and spelling outcomes are discussed. Suggestions for the classroom acoustic conditions needed to ensure appropriate literacy development and areas for future research are also considered.